(untitled) (KIUT Publication, 2025)
Myocardial infarction (MI) is a necrotic process that develops as a result of sudden and severe ischemia of the heart muscle and is one of the leading causes of death among cardiovascular diseases worldwide. In this condition, analyzing the morphological and histological changes in myocardial tissues plays a crucial role, especially in determining the stage of the disease and selecting appropriate treatment strategies. In our study, histological and ultrastructural changes in infarcted areas were identified based on heart biopsies, using classical staining techniques and electron microscopic analysis.